Comparative studies of fungal degradation of single or mixed bioaccessible reactive azo dyes - Martins, M. Adosinda M. (2003)
A screening using several fungi (Phanerochaete chrysosporium, Pleurotus ostreatus, Trametes versicolor and Aureobasidium pullulans) was performed on the degradation of syringol derivatives of azo dyes possessing either carboxylic or sulphonic groups, under optimized conditions previously established by us. T. versicolor showed the best biodegradation performance and its potential was confirmed by the degradation of differently substituted fungal bioaccessible dyes. Enzymatic assays (lignin peroxidase, manganese peroxidase, laccase, proteases and glyoxal oxidase) and GC-MS analysis were performed upon the assay obtained using the most degraded dye. The identification of hydroxylated metabolites allowed us to propose a possible metabolic pathway. Biodegradation assays using mixtures of these bioaccessible dyes were performed to evaluate the possibility of a fungal wastewater treatment for textile industries.